The Unknown George (Giorgi) Papashvily - Rusudan Nishnianidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The paper deals with the Georgian born wel-known American sculptor and writer George (Giorgi) Papashvily. His works are preserved in state museums alid private collections. His book "Anything Can Happen", written in co-authorship with his wife Helen Waite Papashvily, was acknowledged a best-seller and called an unprecedented event: George Papashviliy's works constitute a landmark in the history of Georgian- American culture.